National geospatial database for Maldives to mainstream climate change adaptation in development planning. - Zheng, Liping (Paper and briefs., 2019)
It explains how technical assistance helped build a geospatial database on coastal and marine ecosystems and how climate risk screening was tested on selected development projects. It highlights lessons and suggests ways forward for policymakers in Maldives.